Effectiveness of Parental Assistance in Providing Food on Nutritional Intake Among Children with Malnutrition - Chabibah, Nur; Khanifah, Milatun; Kristiyanti, Rini (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2021)
Background: Prevalence of stunting continues to affect 21.3% of children aged <5 years worldwide. The problem of malnutrition in children is caused by several factors, such as poor access to nutritious food, recurrent infections, and inadequate practice of offering food and care for mothers and children during the first 1,000 days.Objectives: The purpose of the study was to know the effectiveness of feeding parenting style assistance to mothers of toddlers in increasing the nutritional intake of under-nutrition childrenMaterials and Methods: This study used a quasi-experimental design with a pre-test and post-test control group design approach. The population in this study was toddlers with malnutrition (according to weight/height). The sample size for each group was 35 mothers. The sample was divided into two groups. The first group was given parental assistance consisting of nutrition education and food processing guidance for the toddler for 3 months (the intervention group) and the second group was given health education about balanced nutrition for children under five (the control group). Collecting data had used a checklist of identity, nutritional status, and semi-quantitative food frequency questionnaire. Data were analyzed using paired t-test, p-value <0.05 for the 95% confidence interval.Results: The nutritional intakes of children under five showed a significant difference between the group of mothers under five who were given intensive assistance (the intervention group) and the group that was only given nutrition education for children under five (the control group). The differences in nutritional intakes seen in macronutrients were the difference in calorie intake (p-value: 0.042; CI: 4.005-213.543) and protein intake (p-value: 0.040; CI: 0.197-8.065). The differences in micronutrient intakes were seen in the increase in consumption of vitamin E (p-value: 0.000; CI: 0.446-4.416), sodium (p-value: 0.000; CI: 61.859-193.741), potassium (p-value: 0.005; CI: 70.743-373.102), calcium (p-value: 0.000; CI: 51.851-137.863), and phosphor (p-value: 0.041; CI: 2.133-99.604).Conclusion: Food parenting assistance for mothers of toddlers was effective in increasing toddler nutrition